Development and validation of the Chinese patient-centered integrated care scale - Yue Yin; Wenqing Gao; Xiujuan Cui; Wenxi Tang (BMC Health Services Research)
Abstract Background The healthcare system is currently facing challenges in transitioning to a more integrated, patient-centered care. China has implemented various practical exploration and pilot programs in developing an integrated healthcare service system. However, there remains an absence of appropriate instrument to assess integrated care from the patient’s perspective, particularly one that aligns with China's national conditions. Methods Using a literature review, Delphi methods, a pilot study involving 171 chronic patients in Guangdong Province, and the analytic hierarchy process, we developed and validated the Chinese Patient-Centered Integrated Care (CPCIC) with a weighting system. Results The results of exploratory factor analysis indicated CPCIC scale had robust structural validity. The overall Cronbach’s α coefficient was 0.868, signifying excellent internal consistency. The final scale included four first-level indicators (dimensions): services responsiveness, services convenience, services continuity and services coordination and 14 s-level indicators (items). The assigned weights of these dimensions were 0.1070, 0.2926, 0.4155 and 0.1849, respectively. Conclusions The four-dimension, 14-item CPCIC scale with a weighting system was successfully developed and validated. The scale provides a reliable and valid instrument for evaluating the degree of integrated care from the patient’s perspective, and has potential applications in informing the reform of China’s healthcare system to enhance patient-centered care.